The impact and effectiveness of the general public wearing masks to reduce the spread of pandemics in the UK: a multidisciplinary comparison of single-use masks versus reusable face masks. Issue 3 (25th August 2021) - Allison, Ayşe Lisa; Ambrose-Dempster, Esther; Bawn, Maria; Arredondo, Miguel Casas; Chau, Charnett; Chandler, Kimberley; Dobrijevic, Dragana; Aparasi, Teresa Domenech; Hailes, Helen C.; Lettieri, Paola; Liu, Chao; Medda, Francesca; et al.
Abstract : During the coronavirus (COVID-19) pandemic, the UK government mandated the use of face masks in various public settings and recommended the use of reusable masks to combat shortages of medically graded single-use masks in healthcare. To assist decision-making on the choice of masks for future pandemics, where shortages may not be a contributing factor, the University College London (UCL) Plastic Waste Innovation Hub has carried out a multidisciplinary comparison between single-use and reusable masks based on their anatomy, standalone effectiveness, behavioural considerations, environmental impact and costs. Although current single-use masks have a higher standalone effectiveness against bacteria and viruses, studies show that reusable masks have adequate performance in slowing infection rates of respiratory viruses. Material flow analysis (MFA), life cycle assessment (LCA) and cost comparison show that reusable masks have a lower environmental and economic impact than single-use masks. If every person in the UK uses one single-use mask each day for a year, it will create a total of 124, 000 tonnes of waste, 66, 000 tonnes of which would be unrecyclable contaminated plastic waste (the masks), with the rest being the recyclable packaging typically used for transportation and distribution of masks. Using reusable masks creates >85% less waste, generates 3.5 times lower impact on climate change and incurs 3.7 times lower costs. Further behavioural research is necessary to understand the extent and current practices of mask use; and how these practices affect mask effectiveness in reducing infection rates. Wearing single-use masks may be preferred over reusable masks due to perceptions of increased hygiene and convenience. Understanding behaviour towards the regular machine-washing of reusable masks for their effective reuse is key to maximise their public health benefits and minimise environmental and economic costs.